2010
DOI: 10.1073/pnas.1005962107
|View full text |Cite
|
Sign up to set email alerts
|

Predicting consumer behavior with Web search

Abstract: Recent work has demonstrated that Web search volume can "predict the present," meaning that it can be used to accurately track outcomes such as unemployment levels, auto and home sales, and disease prevalence in near real time. Here we show that what consumers are searching for online can also predict their collective future behavior days or even weeks in advance. Specifically we use search query volume to forecast the opening weekend box-office revenue for feature films, first-month sales of video games, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
341
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(362 citation statements)
references
References 16 publications
4
341
1
8
Order By: Relevance
“…However, predicting hit-songs may always be a particularly difficult task. A recent study of internet searches found good predictability for revenue of movies and video games but less so for music (Goel, Hofman, Lahaie, Pennock, & Watts, 2010), which makes our results even more surprising and refutes the idea that hits are random (Bielby & Bielby, 1994).…”
Section: Discussionsupporting
confidence: 41%
“…However, predicting hit-songs may always be a particularly difficult task. A recent study of internet searches found good predictability for revenue of movies and video games but less so for music (Goel, Hofman, Lahaie, Pennock, & Watts, 2010), which makes our results even more surprising and refutes the idea that hits are random (Bielby & Bielby, 1994).…”
Section: Discussionsupporting
confidence: 41%
“…Search data of prominent retailers were examined and a positive correlation with both store and online performance was identified, which can be an indicator for total brand performance. This is also confirmed by [9]which found that search query volume can be very predictive of future outcomes.…”
Section: Related Worksupporting
confidence: 55%
“…Web search data can "predict the present" by providing evidence on time-varying outcomes more quickly than other methods (Ginsberg et al 2008;Choi and Varian 2012;Varian 2014; but see also Lazer et al 2014). Scholars have also used web search data to predict consumer behavior into the near future (Goel et al 2010).…”
Section: The Effects Of Electoral Rulesmentioning
confidence: 99%